(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research investigates the evolution of consumption in Samsung Android mobile handsets over the past decade, with a focus on identifying trends and analysing consumer behaviour. Data was collected from 300 respondents through a questionnaire. Statistical tools, including regression analysis, ANOVA, and chi-square tests, were applied to understand the factors influencing consumer preferences and satisfaction. The study provides valuable insights into how consumer behaviour has evolved and offers recommendations for marketers and policymakers.